A kind of enhanced hydrophobic polypropylene hollow fiber composite membrane and preparation method thereof

The enhanced hydrophobic polypropylene hollow fiber composite membrane was prepared through concentric circle composite spinning technology, which solved the shortcomings of oil-containing wastewater treatment equipment in the prior art and the performance limitations of hollow fiber membranes, and achieved high-strength, good hydrophobicity and long-life membrane materials, expanding its application range.

CN118179292BActive Publication Date: 2025-03-11SHANGHAI UNIV OF ENG SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410532181.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-29
Publication Date
2025-03-11
Estimated Expiration
2044-04-29

AI Technical Summary

Technical Problem

The existing oil-containing sewage treatment technology has weaknesses such as long time, large equipment size, fast equipment corrosion rate, and the use of a large number of chemical agents. The mechanical properties, acid and alkali resistance and chemical reagent resistance of hollow fiber microporous membranes are poor, which limits its application in oil-containing sewage treatment and other fields.

Method used

The enhanced hydrophobic polypropylene hollow fiber composite film is prepared by using concentric circle composite spinning technology. By combining the cast film liquid with the hollow braided tube and cooling it into a molding through an air bath and a water solidification bath, a composite film with a reinforced body surface separation layer is formed.

Benefits of technology

It improves the strength and hydrophobicity of the polypropylene hollow fiber membrane, improves the mechanical properties and anti-pollution properties of the membrane fiber, extends the service life of the membrane fiber, and expands its application range in oil-containing wastewater treatment and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118179292B_ABST
    Figure CN118179292B_ABST
Patent Text Reader

Abstract

The present invention discloses an enhanced hydrophobic polypropylene hollow fiber composite membrane and a preparation method thereof. The method comprises: (1) providing a casting solution containing polypropylene, a hydrophobic additive, an emulsifier and a diluent; (2) using a concentric circle composite spinning method to allow the casting solution to be bonded to the outer surface of a tubular reinforcing body. The method can effectively improve the hydrophobicity of the polypropylene hollow fiber composite membrane and improve its mechanical properties, so that the obtained hollow fiber composite membrane can meet the needs of application scenarios such as oil-water separation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of membrane separation materials, and particularly relates to an enhanced hydrophobic polypropylene hollow fiber composite membrane and a preparation method thereof. Background Art

[0002] Oily wastewater comes from a wide range of sources. In the petrochemical industry, crude oil extraction and processing, oil storage, tanker leakage, marine oil spills, etc. will produce a lot of oily wastewater. If these oily wastewater cannot be effectively treated, it will cause huge losses and long-term harm to the economy, human health and the environment. Existing oily wastewater treatment technologies such as gravity separation, centrifugation, filtration, flotation, etc. have weaknesses such as long existence time, large equipment size, fast equipment corrosion rate, and the use of large amounts of chemical agents.

[0003] Membrane separation technology is a new separation technology formed by the cross-integration of multiple disciplines such as materials, textiles, chemicals, and environment. It has the characteristics of high efficiency, environmental protection, and energy saving, and has played an important role in solving the oil pollution crisis, environmental and energy problems, etc. Hollow fiber microporous membranes are mostly prepared by solution phase conversion method, such as polysulfone, polyethersulfone, polyvinylidene fluoride, etc., but these membranes often have poor mechanical properties, acid and alkali resistance, and chemical reagent resistance. The application is limited in many fields, such as oil-containing wastewater treatment, purification or purification of organic solvents, filtration of acidic or alkaline liquids, MBR system treatment of sewage, etc.

[0004] Polypropylene (PP) is a non-toxic, odorless white powder or granule with a milky white appearance. It has good chemical stability, thermal stability and hydrophobicity, good mechanical properties, easy-to-obtain raw materials, and low price. It is also one of the most widely used polymer membrane materials. However, PP is a semi-crystalline polymer that is insoluble in any organic solvent at room temperature, so the traditional solution phase inversion method cannot be used to prepare PP hollow fiber membranes. PP is a thermoplastic polymer that can form a homogeneous solution with certain solvents at high temperatures. PP hollow fiber membranes can usually be prepared by melt spinning-stretching (MS-S) and thermally induced phase separation (TIPS) methods. Although the MS-S method does not require the addition of any organic solvents during the spinning and membrane-making process and is environmentally friendly, the prepared hollow fiber membranes have large capillary pores, a wide pore size distribution, and are difficult to control. The pore size is relatively low, and the tensile strength is relatively low, so its application is limited to a certain extent. Although the PP hollow fiber membrane prepared by the TIPS method has a narrow pore size distribution, the tensile strength of the membrane is still low. In the environment of treating oily wastewater, long-term pressure from high-pressure water flow, aeration impact disturbance, and frequent cleaning will cause great damage to the membrane fibers, which are prone to problems such as membrane fiber breakage or breakage, seriously affecting the reliability and service life of the membrane operation. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and to briefly introduce some preferred embodiments.

[0006] As one aspect of the present invention, the present invention provides a method for preparing a reinforced hydrophobic polypropylene hollow fiber composite membrane, which comprises:

[0007] (1) preparing a casting solution containing polypropylene, a hydrophobic additive, an emulsifier and a diluent;

[0008] (2) using a concentric composite spinning method, with a twin screw extruder as the extruder and a hollow braided tube as the reinforcement, so that the casting liquid is combined with the outer surface of the reinforcement, and then cooled and formed in an air bath and a water coagulation bath, and after being fully solidified, a primary polypropylene hollow fiber membrane is obtained;

[0009] (3) The nascent polypropylene hollow fiber membrane is immersed in an extractant and dried to prepare a composite reinforced polypropylene hollow fiber composite membrane consisting of a reinforcement body and a polypropylene surface separation layer.

[0010] As a preferred embodiment of the method of the present invention: in step (1), the mass fraction composition of the casting solution is: 12-20% polypropylene resin, 5-15% hydrophobic additive, 0.5-5% emulsifier, and the balance is diluent.

[0011] As a preferred embodiment of the method of the present invention: in step (1), the hydrophobic additive comprises a polymer additive and an inorganic additive, the polymer additive is selected from at least one of methyl methacrylate-methyl acrylate copolymer, styrene-methyl acrylate copolymer, fluorine-containing acrylic copolymer, and polypropylene-cysteine ​​copolymer, and the inorganic additive is selected from at least one of graphene, hydrophobic silica, hydrophobic titanium dioxide, and hydrophobic zinc oxide.

[0012] As a preferred embodiment of the method of the present invention: in step (1), the emulsifier is selected from at least one of octanol polyoxyethylene ether, nonylphenol polyoxyethylene ether, octylphenol polyoxyethylene ether, and alcohol polyoxyethylene ether; and the diluent is selected from at least one of soybean oil, white oil, phthalate, kerosene, and liquid paraffin.

[0013] As a preferred embodiment of the method of the present invention: in step (1), the mass fraction of the inorganic additive is 1.3-2%; the mass fraction of graphene is 0.1-2%; and the mass fraction of the polymer additive is 3-10%.

[0014] As a preferred embodiment of the method of the present invention: the method for preparing the casting solution in step (1) comprises: mixing a diluent, an emulsifier, and a hydrophobic additive, and ultrasonically dispersing the mixture, and mixing the obtained mixture with polypropylene to obtain the casting solution;

[0015] The mixing is carried out by a homogenizer dispersion method; the ultrasonic dispersion is carried out by an ultrasonic cleaning machine oscillation dispersion method;

[0016] The mixing conditions are as follows: the speed of the homogenizer is 1000-8000 r / min, the time is 10-60 min; the ultrasonic power is 400-800 W, and the ultrasonic time is 10-60 min.

[0017] As a preferred embodiment of the method described in the present invention: in step (2), the hollow braided tube is a hollow fiber braided tube, which is a fiber braided tube made of at least one of polyester fiber, polyamide fiber, polypropylene fiber and polyethylene fiber with a crocheted or woven structure; the outer diameter of the hollow fiber braided tube is 0.6-2mm, the wall thickness is 0.1-0.3mm, and the density is 20-40 mesh.

[0018] As a preferred embodiment of the method described in the present invention: in step (2), the conditions of the concentric composite spinning include: a spinning temperature of 150-230°C, a spinning speed of 6-25m / min, a contact distance between the casting liquid and the reinforcement at the spinneret of 2-8cm; the air bath temperature of 20-30°C; and the coagulation bath temperature of 10-40°C.

[0019] As a preferred embodiment of the method of the present invention: in step (3), the extractant is selected from at least one of dichloromethane, n-hexane and hydrocarbon cleaning agent.

[0020] Beneficial effects of the present invention:

[0021] (1) The polypropylene hollow fiber composite membrane obtained by the method provided by the present invention is composed of a surface separation layer with an internal reinforcement body partially embedded in the reinforcement body, which effectively improves the strength of the polypropylene hollow fiber membrane and improves the mechanical properties of the membrane fiber. At the same time, due to the use of a suitable hydrophobic additive in the surface separation layer, the hydrophobicity of the hollow fiber composite membrane is improved. The hollow fiber composite membrane fully meets the requirements of the oil-water separation process for the mechanical properties of the membrane fiber, and has good hydrophobicity, which expands the application range of the polypropylene hollow fiber membrane;

[0022] (2) In the method provided by the present invention, no core liquid is required inside the fiber braided tube cavity during the spinning process, the thickness of the external separation layer is controllable, the preparation process is simple and easy to operate, and the quality stability can also be guaranteed;

[0023] (3) In the method provided by the present invention, the hydrophobic additive is blended with polypropylene to solve the problem of insufficient hydrophobicity of the melt-spinning-stretching polypropylene hollow fiber membrane, improve the anti-pollution performance of the membrane fiber, and extend the service life of the membrane fiber. The hydrophobicization process of the present invention is simple, low-cost, and easy to apply on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the following briefly introduces the drawings required for describing the embodiment, wherein:

[0025] Figure 1 This is an electron microscope image of the cross-section of the polypropylene hollow fiber composite membrane A1 obtained in Example 1 of the present invention.

[0026] Figure 2 This is a partially enlarged electron microscope image of the cross section of the polypropylene hollow fiber composite membrane A1 obtained in Example 1 of the present invention.

[0027] Figure 3 This is an electron microscope image of the outer surface of the polypropylene hollow fiber composite membrane A1 obtained in Example 1 of the present invention.

[0028] Figure 4 This is a partially enlarged electron microscope image of the cross section of the polypropylene hollow fiber composite membrane A4 obtained in Example 4 of the present invention.

[0029] Figure 5 This is a partially enlarged electron microscope image of the cross section of the polypropylene hollow fiber composite membrane A6 obtained in Example 6 of the present invention. DETAILED DESCRIPTION

[0030] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.

[0031] The following experimental materials are used:

[0032] Polypropylene (article number K8303 purchased from Beijing Yanshan Petrochemical); methyl methacrylate-methyl acrylate copolymer (co-MMA-MA: MMA and MA feed mass ratio is 9:1, China Petroleum Jilin Petrochemical Company Research Institute); hydrophobic silica (average particle size 12nm, article number 1408141618, Beijing Boyu High-tech New Materials Technology Co., Ltd., hydrophobic fumed silica obtained by DDS post-treatment (dimethyldichlorosilane surface treatment agent)); hydrophobic titanium dioxide (model NYTi20, Beijing Boyu High-tech New Materials Technology Co., Ltd.); graphene (TA-001A, Xiamen Kaina Graphene Technology Co., Ltd.); octanol polyoxyethylene ether (AEO-3, Hai'an Petrochemical Plant, Jiangsu Province); soybean oil (Golden Dragon Fish)

[0033] Preparation method of methacrylic acid-acrylamide copolymer: (acrylamide (AAM) 79-06-1, Shanghai Gaoxin Chemical Glass Instrument Co., Ltd.; methacrylic acid (MAA) 79-41-4, Sinopharm Chemical Reagent Co., Ltd.). Prepare 1 mol·L -1 The aqueous solution of acrylamide is mixed with methacrylic acid to prepare a mixed solution containing monomers AAM:MAA in a molar ratio of 1:1. The solution is poured into a watch glass and placed in an irradiation box with a power of 1000 W and a wavelength of 365 nm, 20 cm away from the lamp tube, for 30 min. After the copolymerization reaction is completed, the solution is dried in a vacuum oven at 40°C to obtain a methacrylic acid-acrylamide copolymer.

[0034] Preparation method of fluorinated acrylic copolymer: fluorinated acrylic copolymer is synthesized by free radical polymerization method. The mass ratio of perfluorooctylethyl methacrylate (CH2=C(CH3)COO(CH2)2(CF2)7CF3) to non-fluorinated octadecyl acrylate monomer (n=18) is 1∶9. 0.6g of initiator BPO is dissolved in 50mL of xylene, and 30mL of initiator xylene solution is added to a four-necked flask equipped with an electric stirrer, a constant pressure funnel, a thermometer and a reflux condenser. After 18g of octadecyl acrylate (0.55mol) is melted into a liquid state in a 50℃ water bath, it is added to the constant pressure funnel and dripped continuously within 2 to 3h. At the end of the reaction, 2g of perfluorooctylethyl methacrylate monomer (i.e. 0.004mol) is added into the reaction system in a one-time manner. After the monomer is dripped, the remaining 20mL of initiator xylene solution is added and kept warm for 3 to 4h. Finally, the temperature is lowered and the material is discharged. The fluorinated acrylic copolymer is obtained.

[0035] Embodiment 1:

[0036] (1) According to the mass fraction composition of polypropylene 15%, hydrophobic silica 1.5wt% (particle size is about 12nm), graphene 0.1%, octanol polyoxyethylene ether (AEO-3) 1%, and soybean oil 82.4wt%, the casting liquid raw material is weighed. First, the hydrophobic additive (hydrophobic silica and graphene) and the emulsifier (AEO-3) are mixed by a homogenizer (the speed of the homogenizer is 6000r / min, and the duration is 20min), and then the obtained mixture is put into an ultrasonic cleaning machine for ultrasonic dispersion (the power of the ultrasonic cleaning machine is 600W, and the duration is 30min), and then the ultrasonic mixture and polypropylene are stirred and mixed by a homogenizer (the speed of the homogenizer is 6000r / min, and the duration is 30min), and a casting liquid is obtained.

[0037] (2) The casting solution was passed through a twin-screw extruder to form a uniform spinning solution at 220°C. Based on the thermally induced phase separation method, the concentric circle composite spinning technology was adopted. The spinning solution spinneret was in contact with a polyester fiber braided tube with an outer diameter of 1.8 mm, a wall thickness of 0.3 mm, and a density of 25 mesh (the spinneret cavity height was 5 cm), and was coated on the outer layer of the braided tube. After being cured in an 8 cm air bath and a 30°C water coagulation bath (path of 3 m), it was wound at a winding speed of 20 m / min, extracted with an extractant of dichloromethane, and dried (25°C, 120 min) to obtain a polypropylene hollow fiber composite membrane A1.

[0038] Embodiment 2:

[0039] (1) According to the mass fraction composition of polypropylene 15%, hydrophobic silica 2wt% (particle size is about 12nm), graphene 0.1%, octanol polyoxyethylene ether (AEO-3) 1%, and soybean oil 81.9wt%, the casting liquid raw material is weighed. First, the hydrophobic additive (hydrophobic silica and graphene) and the emulsifier (AEO-3) are mixed by a homogenizer (the speed of the homogenizer is 6000r / min, and the duration is 20min), and then the obtained mixture is put into an ultrasonic cleaning machine for ultrasonic dispersion (the power of the ultrasonic cleaning machine is 600W, and the duration is 30min), and then the ultrasonic mixture and polypropylene are stirred and mixed by a homogenizer (the speed of the homogenizer is 6000r / min, and the duration is 30min), and a casting liquid is obtained.

[0040] (2) The casting solution is passed through a twin-screw extruder to form a uniform spinning solution at 220°C. Based on the thermally induced phase separation method, a concentric circle composite spinning technology is adopted. The spinning solution spinneret is in contact with a polyester fiber braided tube with an outer diameter of 1.8 mm, a wall thickness of 0.3 mm, and a density of 25 mesh (the spinneret cavity height is 5 cm), and is coated on the outer layer of the braided tube. After being cured in an 8 cm air bath and a 30°C water coagulation bath (path is 3 m), it is wound at a winding speed of 20 m / min, extracted with an extractant dichloromethane, and dried (25°C, 120 min) to obtain a polypropylene hollow fiber composite membrane A2.

[0041] Embodiment 3:

[0042] (1) According to the mass fraction composition of polypropylene 15%, hydrophobic silica 1.5wt% (particle size is about 12nm), graphene 0.5%, octanol polyoxyethylene ether (AEO-3) 1%, and soybean oil 82wt%, the raw material of the casting liquid is weighed. First, the hydrophobic additive (hydrophobic silica and graphene) and the emulsifier (AEO-3) are mixed by a homogenizer (the speed of the homogenizer is 6000r / min, and the duration is 20min), and then the obtained mixture is put into an ultrasonic cleaning machine for ultrasonic dispersion (the power of the ultrasonic cleaning machine is 600W, and the duration is 30min), and then the ultrasonic mixture and polypropylene are stirred and mixed by a homogenizer (the speed of the homogenizer is 6000r / min, and the duration is 30min) to obtain a casting liquid.

[0043] (2) The casting solution was passed through a twin-screw extruder to form a uniform spinning solution at 220°C. Based on the thermally induced phase separation method, the concentric circle composite spinning technology was adopted. The spinning solution spinneret was in contact with a polyester fiber braided tube with an outer diameter of 1.8 mm, a wall thickness of 0.3 mm, and a density of 25 mesh (the spinneret cavity height was 5 cm), and was coated on the outer layer of the braided tube. After being cured in an 8 cm air bath and a 30°C water coagulation bath (path of 3 m), it was wound at a winding speed of 20 m / min, extracted with an extractant of dichloromethane, and dried (25°C, 120 min) to obtain a polypropylene hollow fiber composite membrane A3.

[0044] Embodiment 4:

[0045] (1) According to the mass fraction composition of polypropylene 15%, methyl methacrylate-methyl acrylate copolymer 5%, hydrophobic silica 1.5wt% (particle size about 12nm), graphene 0.5%, octanol polyoxyethylene ether (AEO-3) 1%, and soybean oil 77wt%, the raw material of the casting liquid is weighed. First, the hydrophobic additive (methyl methacrylate-methyl acrylate copolymer, hydrophobic silica and graphene) and the emulsifier (AEO-3) are mixed by a homogenizer (the speed of the homogenizer is 6000r / min, and the duration is 20min), and then the obtained mixture is put into an ultrasonic cleaning machine for ultrasonic dispersion (the power of the ultrasonic cleaning machine is 600W, and the duration is 30min), and then the ultrasonic mixture and polypropylene are stirred and mixed by a homogenizer (the speed of the homogenizer is 6000r / min, and the duration is 30min) to obtain a casting liquid.

[0046] (2) The casting solution was passed through a twin-screw extruder to form a uniform spinning solution at 220°C. Based on the thermally induced phase separation method, the concentric circle composite spinning technology was adopted. The spinning solution was contacted with a polyester fiber braided tube with an outer diameter of 1.8 mm, a wall thickness of 0.3 mm, and a density of 25 meshes through a spinneret (the spinneret cavity height was 5 cm), and then coated on the outer layer of the braided tube. After being cured in an 8 cm air bath and a 30°C water coagulation bath (path of 3 m), it was wound at a winding speed of 20 m / min, extracted with an extractant of dichloromethane, and dried (25°C, 120 min) to obtain a polypropylene hollow fiber composite membrane A4.

[0047] Embodiment 5:

[0048] (1) According to the mass fraction composition of polypropylene 15%, fluorinated acrylic copolymer 5%, hydrophobic titanium dioxide 2wt% (particle size about 20nm), graphene 0.5%, octanol polyoxyethylene ether (AEO-3) 1%, and soybean oil 76.5wt%, the casting liquid raw material is weighed. First, the hydrophobic additive (fluorinated acrylic copolymer, hydrophobic titanium dioxide and graphene) and the emulsifier (AEO-3) are mixed by a homogenizer (the speed of the homogenizer is 6000r / min, and the duration is 20min), and then the obtained mixture is put into an ultrasonic cleaning machine for ultrasonic dispersion (the power of the ultrasonic cleaning machine is 600W, and the duration is 30min), and then the ultrasonic mixture and polypropylene are stirred and mixed by a homogenizer (the speed of the homogenizer is 6000r / min, and the duration is 30min), and the casting liquid is obtained.

[0049] (2) The casting solution was passed through a twin-screw extruder to form a uniform spinning solution at 220°C. Based on the thermally induced phase separation method, a concentric circle composite spinning technology was adopted. The spinning solution spinneret was in contact with a polyester fiber braided tube with an outer diameter of 1.8 mm, a wall thickness of 0.3 mm, and a density of 25 mesh (the spinneret cavity height was 5 cm), and was coated on the outer layer of the braided tube. After being cured in an 8 cm air bath and a 30°C water coagulation bath (path of 3 m), it was wound at a winding speed of 20 m / min, extracted with an extractant of dichloromethane, and dried (25°C, 120 min) to obtain a polypropylene hollow fiber composite membrane A5.

[0050] Embodiment 6:

[0051] (1) According to the mass fraction composition of polypropylene 15%, methacrylic acid-acrylamide copolymer 5%, hydrophobic titanium dioxide 2wt% (particle size is about 12nm), graphene 0.5%, octanol polyoxyethylene ether (AEO-3) 1%, and soybean oil 76.5wt%, the casting liquid raw material is weighed. First, the hydrophobic additive (fluorinated acrylic copolymer, hydrophobic titanium dioxide and graphene) and the emulsifier (AEO-3) are mixed by a homogenizer (the speed of the homogenizer is 6000r / min, and the duration is 20min), and then the obtained mixture is put into an ultrasonic cleaning machine for ultrasonic dispersion (the power of the ultrasonic cleaning machine is 600W, and the duration is 30min), and then the ultrasonic mixture and polypropylene are stirred and mixed by a homogenizer (the speed of the homogenizer is 6000r / min, and the duration is 30min) to obtain a casting liquid.

[0052] (2) The casting solution was passed through a twin-screw extruder to form a uniform spinning solution at 220°C. Based on the thermally induced phase separation method, the concentric circle composite spinning technology was adopted. The spinning solution spinneret was in contact with a polyester fiber braided tube with an outer diameter of 1.8 mm, a wall thickness of 0.3 mm, and a density of 25 mesh (the spinneret cavity height was 5 cm), and was coated on the outer layer of the braided tube. After being cured in an 8 cm air bath and a 30°C water coagulation bath (path of 3 m), it was wound at a winding speed of 20 m / min, extracted with an extractant of dichloromethane, and dried (25°C, 120 min) to obtain a polypropylene hollow fiber composite membrane A6.

[0053] Comparative Example 1:

[0054] (1) According to the mass fraction composition of polypropylene 15%, hydrophobic silica 3wt% (particle size is about 12nm), graphene 0.1%, octanol polyoxyethylene ether (AEO-3) 1%, and soybean oil 80.9wt%, the casting liquid raw material is weighed. First, the hydrophobic additive (hydrophobic silica and graphene) and the emulsifier (AEO-3) are mixed by a homogenizer (the speed of the homogenizer is 6000r / min, and the duration is 20min), and then the obtained mixture is put into an ultrasonic cleaning machine for ultrasonic dispersion (the power of the ultrasonic cleaning machine is 600W, and the duration is 30min), and then the ultrasonic mixture and polypropylene are stirred and mixed by a homogenizer (the speed of the homogenizer is 6000r / min, and the duration is 30min), and a casting liquid is obtained.

[0055] (2) The casting solution was passed through a twin-screw extruder to form a uniform spinning solution at 220°C. Based on the thermally induced phase separation method, the concentric circle composite spinning technology was adopted. The spinning solution spinneret was in contact with a polyester fiber braided tube with an outer diameter of 1.8 mm, a wall thickness of 0.3 mm, and a density of 25 mesh (the spinneret cavity height was 5 cm), and was coated on the outer layer of the braided tube. After being cured in an 8 cm air bath and a 30°C water coagulation bath (path of 3 m), it was wound at a winding speed of 20 m / min, extracted with an extractant of dichloromethane, and dried (25°C, 120 min) to obtain a polypropylene hollow fiber composite membrane B1.

[0056] During the experiment, it was found that the formula contained too much silica, resulting in excessive viscosity, uneven dispersion of the components in the casting liquid, and difficulty in spinning.

[0057] Comparative Example 2:

[0058] (1) According to the mass fraction composition of polypropylene 15%, hydrophobic silica 1.5wt% (particle size is about 12nm), graphene 3%, octanol polyoxyethylene ether (AEO-3) 1%, and soybean oil 79.5wt%, the casting liquid raw material is weighed. First, the hydrophobic additive (hydrophobic silica and graphene) and the emulsifier (AEO-3) are mixed by a homogenizer (the speed of the homogenizer is 6000r / min, and the duration is 20min), and then the obtained mixture is put into an ultrasonic cleaning machine for ultrasonic dispersion (the power of the ultrasonic cleaning machine is 600W, and the duration is 30min), and then the ultrasonic mixture and polypropylene are stirred and mixed by a homogenizer (the speed of the homogenizer is 6000r / min, and the duration is 30min), and a casting liquid is obtained.

[0059] (2) The casting solution was passed through a twin-screw extruder to form a uniform spinning solution at 220°C. Based on the thermally induced phase separation method, the concentric circle composite spinning technology was adopted. The spinning solution spinneret was in contact with a polyester fiber braided tube with an outer diameter of 1.8 mm, a wall thickness of 0.3 mm, and a density of 25 mesh (the spinneret cavity height was 5 cm), and was coated on the outer layer of the braided tube. After being cured in an 8 cm air bath and a 30°C water coagulation bath (path of 3 m), it was wound at a winding speed of 20 m / min, extracted with an extractant of dichloromethane, and dried (25°C, 120 min) to obtain a polypropylene hollow fiber composite membrane B2.

[0060] During the experiment, it was found that the formula contained too much graphene, resulting in excessive viscosity, uneven dispersion of the components in the casting liquid, and difficulty in spinning.

[0061] Comparative Example 3:

[0062] (1) According to the mass fraction composition of polypropylene 10%, hydrophobic silica 1.5wt% (particle size is about 12nm), graphene 0.5%, octanol polyoxyethylene ether (AEO-3) 1%, and soybean oil 87wt%, the casting liquid raw material is weighed. First, the hydrophobic additive (hydrophobic silica and graphene) and the emulsifier (AEO-3) are mixed by a homogenizer (the speed of the homogenizer is 6000r / min, and the duration is 20min), and then the obtained mixture is put into an ultrasonic cleaning machine for ultrasonic dispersion (the power of the ultrasonic cleaning machine is 600W, and the duration is 30min), and then the ultrasonic mixture and polypropylene are stirred and mixed by a homogenizer (the speed of the homogenizer is 6000r / min, and the duration is 30min), and the casting liquid is obtained.

[0063] (2) The casting solution was passed through a twin-screw extruder to form a uniform spinning solution at 220°C. Based on the thermally induced phase separation method, the concentric circle composite spinning technology was adopted. The spinning solution spinneret was in contact with a polyester fiber braided tube with an outer diameter of 1.8 mm, a wall thickness of 0.3 mm, and a density of 25 mesh (the spinneret cavity height was 5 cm), and was coated on the outer layer of the braided tube. After being cured in an 8 cm air bath and a 30°C water coagulation bath (path of 3 m), it was wound at a winding speed of 20 m / min, extracted with an extractant of dichloromethane, and dried (25°C, 120 min) to obtain a polypropylene hollow fiber composite membrane B3.

[0064] During the experiment, it was found that the formula had a low solid content and poor film-forming properties and could not be tested.

[0065] Comparative Example 4:

[0066] (1) According to the mass fraction composition of polypropylene 15%, fluorinated acrylic copolymer 5%, hydrophobic silica 2wt% (particle size about 12nm), graphene 0.5%, octanol polyoxyethylene ether (AEO-3) 1%, and soybean oil 76.5wt%, the casting liquid raw material is weighed. First, the hydrophobic additive (fluorinated acrylic copolymer, hydrophobic silica and graphene) and the emulsifier (AEO-3) are mixed by a homogenizer (the speed of the homogenizer is 6000r / min, and the duration is 20min), and then the obtained mixture is put into an ultrasonic cleaning machine for ultrasonic dispersion (the power of the ultrasonic cleaning machine is 600W, and the duration is 30min), and then the ultrasonic mixture and polypropylene are stirred and mixed by a homogenizer (the speed of the homogenizer is 6000r / min, and the duration is 30min), and the casting liquid is obtained.

[0067] (2) The casting solution was passed through a twin-screw extruder to form a uniform spinning solution at 220°C. Based on the thermally induced phase separation method, the concentric circle composite spinning technology was adopted. The spinning solution spinneret was in contact with a polyester fiber braided tube with an outer diameter of 1.8 mm, a wall thickness of 0.3 mm, and a density of 25 mesh (the spinneret cavity height was 5 cm), and was coated on the outer layer of the braided tube. After being cured in an 8 cm air bath and a 30°C water coagulation bath (path of 3 m), it was wound at a winding speed of 20 m / min, extracted with an extractant of dichloromethane, and dried (25°C, 120 min) to obtain a polypropylene hollow fiber composite membrane B4.

[0068] Comparative Example 5:

[0069] (1) According to the mass fraction composition of polypropylene 15%, fluorinated acrylic copolymer 15%, hydrophobic silica 2wt% (particle size about 12nm), graphene 0.5%, octanol polyoxyethylene ether (AEO-3) 1%, and soybean oil 66.5wt%, the casting liquid raw material is weighed. First, the hydrophobic additive (fluorinated acrylic copolymer, hydrophobic silica and graphene) and the emulsifier (AEO-3) are mixed by a homogenizer (the speed of the homogenizer is 6000r / min, and the duration is 20min), and then the obtained mixture is put into an ultrasonic cleaning machine for ultrasonic dispersion (the power of the ultrasonic cleaning machine is 600W, and the duration is 30min), and then the ultrasonic mixture and polypropylene are stirred and mixed by a homogenizer (the speed of the homogenizer is 6000r / min, and the duration is 30min), and the casting liquid is obtained.

[0070] (2) The casting solution was passed through a twin-screw extruder to form a uniform spinning solution at 220°C. Based on the thermally induced phase separation method, the concentric circle composite spinning technology was adopted. The spinning solution spinneret was in contact with a polyester fiber braided tube with an outer diameter of 1.8 mm, a wall thickness of 0.3 mm, and a density of 25 mesh (the spinneret cavity height was 5 cm), and was coated on the outer layer of the braided tube. After being cured in an 8 cm air bath and a 30°C water coagulation bath (path of 3 m), it was wound at a winding speed of 20 m / min, extracted with an extractant of dichloromethane, and dried (25°C, 120 min) to obtain a polypropylene hollow fiber composite membrane B5.

[0071] This embodiment increases the content of the copolymer, so that the solid content of the formula increases accordingly. Too high a solid content causes the membrane pore size to become smaller and the interconnected pore channels to close, thereby affecting the oil flux.

[0072] Comparative Example 6:

[0073] (3) According to the mass fraction composition of polypropylene 15%, hydrophobic silica 1.5wt% (particle size is about 12nm), graphene 1%, octanol polyoxyethylene ether (AEO-3) 1%, and soybean oil 81.5wt%, the casting liquid raw material is weighed. First, the hydrophobic additive (hydrophobic silica and graphene) and the emulsifier (AEO-3) are mixed by a homogenizer (the speed of the homogenizer is 6000r / min, and the duration is 20min), and then the obtained mixture is put into an ultrasonic cleaning machine for ultrasonic dispersion (the power of the ultrasonic cleaning machine is 600W, and the duration is 30min), and then the ultrasonic mixture and polypropylene are stirred and mixed by a homogenizer (the speed of the homogenizer is 6000r / min, and the duration is 30min) to obtain a casting liquid.

[0074] (4) The casting solution was passed through a twin-screw extruder to form a uniform spinning solution at 220°C. Based on the thermally induced phase separation method, the concentric circle composite spinning technology was adopted. The spinning solution spinneret was in contact with a polyester fiber braided tube with an outer diameter of 1.8 mm, a wall thickness of 0.3 mm, and a density of 25 mesh (the spinneret cavity height was 5 cm), and was coated on the outer layer of the braided tube. After being cured in an 8 cm air bath and a 30°C water coagulation bath (path of 3 m), it was wound at a winding speed of 20 m / min, extracted with an extractant of dichloromethane, and dried (25°C, 120 min) to obtain a polypropylene hollow fiber composite membrane B6.

[0075] The increase in the proportion of graphene affects the pore structure and oil flux, so the optimal content is 0.5%.

[0076] Test example:

[0077] The average pore size, pore size distribution range, breaking strength, water contact angle and pure oil flux (test pressure -0.09 MPa) of the polypropylene hollow fiber composite membrane obtained in the above examples and comparative examples were tested using an pore size tester, a tensile machine, a water contact angle meter and an oil flux tester. The test results are shown in Table 1.

[0078] Mechanical properties test:

[0079] The breaking strength and breaking elongation of the reinforced PE hollow fiber membrane were measured using an electronic tensile testing machine (TBDL-200N, China). The length of the hollow fiber membrane sample was 150-200 mm, and the effective length between the clamps was 100 mm. The membrane sample was fixed on the clamp, and the hollow fiber membrane was wrapped with non-woven fabric at the clamp to prevent the clamp from damaging the sample. The initial distance and tensile speed were set to 100 mm / min, respectively. -1 and 50mm min -1 The tensile machine was run until the film sample broke in the middle. Each sample was measured 5 times at different positions and the average value was taken to calculate the breaking strength and breaking elongation.

[0080] Penetration performance:

[0081] The static contact angle of PP / GE hollow fiber membrane was measured using an optical contact angle meter. During the titration process, the volume of the droplet was fixed at 0.5ul, and the average value was taken after multiple measurements.

[0082] The flux of the hollow fiber membrane was measured using a flux test device at a working pressure of -0.09 MPa and at 25°C. The membrane flux was calculated using formula (1).

[0083]

[0084] Where J is the pure oil (kerosene) flux (L·m -2 ·h -1 ); V is the filtrate volume (L); S is the membrane area (m 2 );T is the filtration time (h).

[0085] 99 ml of oil (one of kerosene / toluene / soybean oil) and 0.1 g of Span 80 were added to a three-necked flask, stirred at high speed for 30 min at room temperature, and then 0.2 ml of deionized water was slowly added dropwise every 30 min. After adding 1 ml, high-speed stirring was continued for 1.5 h. Finally, uniformly mixed kerosene-in-water emulsion, toluene-in-water emulsion and soybean oil-in-water emulsion were obtained. All prepared emulsions can be stably stored for one week without demulsification, sedimentation and stratification. Test: The oil-water separation performance of PP / GE was tested using a flux device at a working pressure of -0.09 MPa and at 25 °C. The separation efficiency was calculated by the following formula (2).

[0086]

[0087] Where R is the oil-water separation efficiency (%); C f and C p The water content (ppm) in the emulsion and the filtrate, respectively. The BYES-2000A micro-moisture meter was used to quantitatively test the test liquid before and after separation, and its water content and separation efficiency were calculated. The average value was taken after 5 tests.

[0088] Copolymers influence pore structure:

[0089] It can be observed from the electron microscope images that the cross-sectional morphology of the composite membranes obtained from Example 1 to Example 5 and Example 6 has obvious changes. With the adjustment of the formula, the doping of the fluorinated acrylic copolymer makes the obtained membrane structure loose and porous, and the cross-section has interconnected pore structures, which provide channels for the transportation of oil molecules and reduce the mass transfer resistance. In Example 6, the composite membrane structure obtained by doping the methacrylic acid-acrylamide copolymer is relatively dense, the hydrophobicity is reduced, and the oil flux is also significantly reduced. Therefore, we can conclude that changing the type of copolymer in the formula will significantly affect the performance of the obtained composite membrane.

[0090] Table 1

[0091]

[0092]

[0093] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a reinforced hydrophobic polypropylene hollow fiber composite membrane, characterized in that: include, (1) preparing a casting solution containing polypropylene, a hydrophobic additive, an emulsifier and a diluent; the mass fraction composition of the casting solution is: 12-20% polypropylene, 5-15% hydrophobic additive, 0.5-5% emulsifier, and the balance is diluent; (2) Using a concentric composite spinning method, a twin-screw extruder and a hollow braided tube as a reinforcement, the casting liquid is combined with the outer surface of the reinforcement, and then cooled and formed in an air bath and a water coagulation bath. After sufficient solidification, a primary polypropylene hollow fiber membrane is obtained; (3) immersing the nascent polypropylene hollow fiber membrane in an extractant, and drying the nascent polypropylene hollow fiber membrane to prepare a composite reinforced polypropylene hollow fiber composite membrane consisting of a reinforcement body and a polypropylene surface separation layer; In step (1), the hydrophobic additive comprises a polymer additive and an inorganic additive, the polymer additive is selected from at least one of methyl methacrylate-methyl acrylate copolymer, styrene-methyl acrylate copolymer, and fluorine-containing acrylic copolymer, and the inorganic additive is selected from at least one of graphene, hydrophobic silica, hydrophobic titanium dioxide, and hydrophobic zinc oxide; wherein the mass fraction of the inorganic additive is 1.3-1.5%; and the mass fraction of the polymer additive is 3-10%.

2. The method according to claim 1, characterized in that: In step (1), the emulsifier is selected from at least one of octanol polyoxyethylene ether, nonylphenol polyoxyethylene ether, octylphenol polyoxyethylene ether, and alcohol polyoxyethylene ether; and the diluent is selected from at least one of soybean oil, white oil, phthalate, kerosene, and liquid paraffin.

3. The method according to claim 1 or 2, characterized in that: The method for preparing the casting solution in step (1) comprises: mixing a diluent, an emulsifier, and a hydrophobic additive, and dispersing the mixture by ultrasonication, and mixing the obtained mixed product with polypropylene to obtain a casting solution; The mixing is carried out by a homogenizer dispersion method; the ultrasonic dispersion is carried out by an ultrasonic cleaning machine oscillation dispersion method; The mixing conditions are as follows: the speed of the homogenizer is 1000-8000 r / min, the time is 10-60 min; the ultrasonic power is 400-800 W, and the ultrasonic time is 10-60 min.

4. The method according to claim 1 or 2, characterized in that: In step (2), the hollow braided tube is a hollow fiber braided tube, which is a fiber braided tube made of at least one of polyester fiber, polyamide fiber, polypropylene fiber and polyethylene fiber in a crocheted or woven structure; the outer diameter of the hollow fiber braided tube is 0.6-2 mm, the wall thickness is 0.1-0.3 mm, and the density is 20-40 mesh.

5. The method according to claim 1 or 2, characterized in that: In step (2), the conditions of the concentric composite spinning include: a spinning temperature of 150-230°C, a spinning speed of 6-25 m / min, a contact distance between the casting solution at the spinneret and the reinforcement of 2-8 cm; the air bath temperature of 20-30°C; and the coagulation bath temperature of 10-40°C.

6. The method according to claim 1 or 2, characterized in that: In step (3), the extractant is selected from at least one of dichloromethane, n-hexane and hydrocarbon cleaning agent.

7. The enhanced hydrophobic polypropylene hollow fiber composite membrane prepared by the method according to claim 1.

Citation Information

Patent Citations

  • Preparation method of composite enhanced polypropylene hollow fiber microporous membrane

    CN115430295A